Relationship between maternal and/or newborn cholesterol levels and neonatal septicemia: protocol for a Ugandan cohort of mother-newborn pairs - Kenneth Ssebambulidde; Anthony Kayiira; Ivan Segawa; Sylvia Namanda; Victoria Nakibuuka; Victor Musiime; Theresa H. Ward (BMC, 2022)
Abstract Background Many aspects of microbial dissemination appear to vary with host cholesterol levels. Since neonatal septicemia remains a leading cause of newborn admissions and mortality in resource-limited settings, the contribution of abnormal cholesterol levels in maternal and/or newborn blood to the risk of neonatal septicemia and outcome requires elucidation. We aim to determine a relationship between maternal serum and neonatal cord blood cholesterol levels and neonatal septicemia. Methods This will be a mother-newborn pair cohort study. Approximately 353 pregnant women who are eligible and consent to participate in the study will have blood drawn for a lipid profile. Upon delivery, we will analyse the cord blood cholesterol of their newborns and follow them for 28 days to determine whether the infants develop clinical signs and symptoms suggestive of neonatal septicemia. Relative risk will be used to determine the association between cholesterol and newborn septicemia. Poisson regression will be used to estimate the relative risk (with 95% confidence intervals) of developing septicemia. Discussion Findings from our study will contribute evidence to support the inclusion of lipid profile screening for pregnant women and newborns. Our study will determine whether newborns with abnormal cholesterol or those born to mothers with abnormal cholesterol will require rigorous follow-up in neonatal clinics.